O desenvolvimento sustentável e sua interpretação jurídica - Marques, José Roberto (2009)
The environmental matter is a topic present in any line of discussion. It is a result of the laws of Biology, Chemistry and Physics, once we can not ignore that next generations quality of life is submitted to them, so, protecting the environment is really valuable. The current environmental degradation has many of its effects deferred to a time we can not precise. This process arises from the inevitability, at the moment, of satisfying the needs of the present generations and allowing them to harvest the benefits of their right to development. In order to do so, it must be considered that the environmental resources are limited and there are no conditions to assure for how long they will serve men. In such context, the role of Law is important, in charge of balancing the environmental preservation and the economic growth, without ignoring the necessary benefit that shall result from it to human being. This scenery constitutes what is called sustainable development. With such a purpose, the operators of Law, when interpreting juridical laws, must consider, first, the laws of nature, adjusting the legislation to them. Then, considering the constitutional orders observing the acknowledged social rights and the individual s dignity principle one has to interpret the rules so that the result favors the collectivity and, as much as possible to do such adjustment, promote the sustainable development. Considering that sustainability only can be ascertained a long time after the action, looking back to the past, the caution in the administration of the environmental resources available (Legislative, Executive and Judiciary Powers activities, each one performing its role), must guide all public and private politics, applying the principles of prevention, precaution and polluter pays